Topological Network Theory and Its Application to LCA and IOA and Related Industrial Ecology Tools: Principles and Promise - Heijungs, Reinout (Journal of Environmental Accounting and Management, 2026)
One way to study complex systems is by methods from topological network theory, that concentrate on the topological structure of the system in terms of vertices (nodes) and edges that connect pairs of vertices. The last two decades, topological network theory has seen a wide range of applications. In this paper, we explore its potential for two of the model systems that are central to industrial ecology (IE): life cycle assessment (LCA) and input-output analysis (IOA), with the aim of finding out whether this theory offers insights that are useful to IE. We describe the principles of topological network theory, as well as the possible rules for translating LCA and IOA systems into a formal network. We apply this theory to two cases, the ecoinvent LCA database, and the monetary IOtable for the European Union in 2007. Our conclusions are mixed. It is not entirely clear what the resulting network indicators imply for a specific LCA case or IOA case. Although the results obtained are perfectly explainable and thus do make sense, they appear to be very sensitive to arbitrary choices, such as the level of aggregation. Moreover, it appears to be difficult to include the environmental aspect in the network analysis, so that we end up with analyzing an industrial network rather than industrial-ecological network.